Microglial immunophenotype in dementia with Alzheimer's pathology. Issue 1 (December 2016) - Minett, Thais; Classey, John; Matthews, Fiona; Fahrenhold, Marie; Taga, Mariko; Brayne, Carol; Ince, Paul; Nicoll, James; Boche, Delphine
Abstract Background Genetic risk factors for Alzheimer's disease imply that inflammation plays a causal role in development of the disease. Experimental studies suggest that microglia, as the brain macrophages, have diverse functions, with their main role in health being to survey the brain parenchyma through highly motile processes. Methods Using the Medical Research Council Cognitive Function and Ageing Studies resources, we have immunophenotyped microglia to investigate their role in dementia with Alzheimer's pathology. Cerebral cortex obtained atpost -mortem from 299 participants was analysed by immunohistochemistry for cluster of differentiation (CD)68 (phagocytosis), human leukocyte antigen (HLA)-DR (antigen-presenting function), ionized calcium-binding adaptor molecule (Iba1) (microglial motility), macrophage scavenger receptor (MSR)-A (plaque-related phagocytosis) and CD64 (immunoglobulin Fcγ receptor I). Results The presence of dementia was associated positively with CD68 (P < 0.001), MSR-A (P = 0.010) and CD64 (P = 0.007) and negatively with Iba1 (P < 0.001). Among participants without dementia, the cognitive function according to the Mini-Mental State Examination was associated positively with Iba1 (P < 0.001) and negatively with CD68 (P = 0.033), and in participants with dementia and Alzheimer's pathology, positively with all microglial markers except Iba1. Overall, in participants without dementia, the relationship with Alzheimer's pathology was negative or not significant, and positive in participants with dementia and Alzheimer's pathology. Apolipoprotein E (APOE ) ε2 allele was associated with expression of Iba1 (P = 0.001) and MSR-A (P < 0.001) andAPOE ε4 with CD68, HLA-DR and CD64 (P < 0.001). Conclusions Our findings raise the possibility that in dementia with Alzheimer's pathology, microglia lose motility (Iba-1) necessary to support neurons. Conversely, other microglial proteins (CD68, MSR-A), the role of which is clearance of damaged cellular material, are positively associated with Alzheimer's pathology and impaired cognitive function. In addition, our data imply that microglia may respond differently to Aβ and tau in participants with and without dementia so that the microglial activity could potentially influence the likelihood of developing dementia, as supported by genetic studies, highlighting the complexity and diversity of microglial responses.